2017
DOI: 10.1007/s00062-017-0571-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Surgical Approach in AVMs Using MRI and 4D DSA Fusion Technique

Abstract: Creating fused images of time-resolved 3D DSA and contrast-enhanced T1-weighted MPRAGE MR images might be beneficial for the preoperative and intrasurgical workflow in patients with AVMs. This new software tool fulfils the required quality and accuracy of the merged images. The clinical validation has to be proven in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Furthermore, they found the LED, determined by fMRI and DTI, to be a single significant predictor of operative risk. Not only did this study report a benefit of modern imaging techniques in bAVM surgery, also DTI of the long association bundles, [3] high-resolution threedimensional multifusion imaging (CT-MRI fusion with combined surface and volume rendering) [46], and MRI fusion with time-resolved (so called 4D) DSA [43] have been reported to be helpful for preoperative planning and intraoperative navigation and eventually to contribute to better surgical outcome.…”
Section: Modern Supratentorial Grading Systemsmentioning
confidence: 76%
“…Furthermore, they found the LED, determined by fMRI and DTI, to be a single significant predictor of operative risk. Not only did this study report a benefit of modern imaging techniques in bAVM surgery, also DTI of the long association bundles, [3] high-resolution threedimensional multifusion imaging (CT-MRI fusion with combined surface and volume rendering) [46], and MRI fusion with time-resolved (so called 4D) DSA [43] have been reported to be helpful for preoperative planning and intraoperative navigation and eventually to contribute to better surgical outcome.…”
Section: Modern Supratentorial Grading Systemsmentioning
confidence: 76%
“…Multimodal imaging fusion at the intracranial level is gaining wider acceptance even though reports remain scarce. 12,[27][28][29] At the aortic arch level, no other reports, to our knowledge, have been published since the pioneering work of Lin et al 15 The VesselNavigator image fusion technique was evaluated in 151 supra-aortic vessels, showing a high spatial accuracy for catheterization at the aortic arch and proximal cervical level. However, we observed that the mismatch increased when reaching distal cervical vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive angioarchitectural information of a cerebral arteriovenous malformation (AVM) can be highly beneficial for risk analysis and treatment planning. 1 Digital subtraction angiography (DSA) remains to be the gold standard for cerebral AVM diagnosis. 2 Conventional clinical assessment typically utilizes a combination of two-dimensional (2D) and three-dimensional (3D) DSA, but rapid vascular filling and vascular overlap in 2D and 3D DSA sometimes compromise the full understand-ing of the cerebral AVM angioarchitecture.…”
Section: Introductionmentioning
confidence: 99%